PELATIHAN DAN PENDAMPINGAN PENGELOLAAN KAMPUNG WISATA LAWAS MASPATI SEBAGAI DESTINASI UNGGULAN BARU SURABAYA - Dian Yulie Reindrawati (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this activity is to improve the ability of the management and residents of Maspati Surabaya Tourism Village on how to manage a tourist destination. This is important considering that as of January 24, 2016, Maspati Surabaya Tourism Village has been officially designated as a New History Leading Destination in Surabaya. Therefore, managers and residents really need knowledge and skills regarding the management of tourist villages absolutely necessary. After the training, they are expected to understand and have knowledge about aspects in managing a destination.